Pullulan-Based Spray-Dried Mucoadhesive Microparticles for Sustained Oromucosal Drug Delivery - Ting Liu; Xiang Gong; Yang Cai; Hao-Ying Li; Ben Forbes (MDPI AG, 2024)
Mucoadhesive microparticles for oromucosal drug delivery offer several advantages, including intimate contact with the mucosa, delivery to less accessible regions, extended residence time, sustained drug release, reduced irritation, and improved patient compliance. In this study, pullulan was used to prepare mucoadhesive spray-dried microparticles for delivering benzydamine hydrochloride (BZH) to oral mucosa. The BZH-pullulan spray-dried microparticles had a mean size of <25 μm with an angle of repose values between 25.8-36.6°. Pullulan markedly extended drug-release time to >180 min, ~9 times greater than the duration (i.e., 20 min) reportedly achieved by chitosan. Kinetic analysis showed the drug-release rate was concentration dependent and jointly controlled by drug diffusion and polymer chain relaxation. Further, pullulan was mucoadhesive and was able to retain up to 78.8% w/w of microencapsulated gold nanoparticle probes at the mucosal membrane. These data strongly suggest that BZH-pullulan microparticles have great potential for oromucosal drug delivery, by providing elongated residence time in situ and sustained drug release for the treatment of local diseases.